Study methods of diploma students in Office System Management in UiTM Seri Iskandar, Perak / Nur Izzati Zulkiflee, Nur Zuhairah Zamberi and Nurshaliza Abdul Kadir - Zulkiflee, Nur Izzati; Zamberi, Nur Zuhairah; Abdul Kadir, Nurshaliza (2010)
This paper investigated the study method of Diploma students in Office System Management in UiTM Perak. Study methods that are chose by the students give a huge impact on their results. This research is done to identify the successes and failures of the study methods applied by the students. It is also to determine the study method used by the students, the student's satisfaction or dissatisfaction on the application of the methods used and the resu Its obtained, the reasons that the study methods are chosen and the impact of the study method on student's study and results. There are 719 students of Diploma in Office System Management in UiTM Seri lskandar. 120 students were selected as the sample and questionnaires were distributed to them. 55.8% of respondents chose self study as their study method followed by 36.7% group discussion, 5.0% mentor or advisor, 1.7% E-Learning and 0.8% library. The recommendation is more stressed on how to overcome the problems towards the study methods that are rarely used by the students. For examples, improve the Internet connection, add more educative materials in the library, mentor or advisor give attention and full support to their students and so forth.